Malignant transformation of mature cystic teratoma - an enigmatic finding in a reproductive woman - Subhransu Kumar Hota; Nikhil Sharma; Pranati Mishra; Ranjana Giri; Kanak Lata Das; Urmila Senapati (Barpeta Obstetrics and Gynaecological Society, 2023)
In the reproductive age group among all ovarian germ cell tumors mature cystic teratoma (MCT) is the most common one. Rarely there is malignant transformation (MT) of MCT with an incidence of 1-3 %. The MT of MCT is mostly in the postmenopausal age group. It is extremely rare in women less than 40 years of age. Here we report a case of 35- year old young female who presented with lower abdominal mass and pain abdomen for the last 4 months radiating to back and left thigh. In ultrasonography there was suspicion of left adnexal mass. Contrast enhanced CT scan (CECT) revealed left adnexal mass possibly malignant transformation of teratoma. All the tumor markers were within normal limits except CA19-9 which was elevated (80U/ml). Extensive surgery was done and samples of hysterectomy, bilateral salpingo-oophorectomy, omentectomy along pelvic and paraaortic lymph nodes were sent for histopathology. Histopathology correlated with radiology and revealed extensive areas of necrosis, the predominant component of squamous cell carcinomatous component along with focal areas showing footprints of benign MCT in the form of clusters of fat cells, few hair shafts intermingled with malignant cells. So the final diagnosis of malignant transformation of mature cystic teratoma in form of squamous cell carcinoma was made. The patient was followed up and was showing partial response to ongoing chemotherapy.